Japanʼs war economy - Pauer, Erich, 1943- (Routledge studies in the growth economies of Asia, 2002)
This book explores the substantial and dynamic innovations of the wartime era, identifying this period as the most influential for Japan's post-war economic structure. Erich Pauer and a team of leading Japanese and German scholars discuss important aspects of the Japanese wartime economy, including:* ideological background* the Japanese 'planned economy'* technical mobilization* women and the war economy* socio-economic change* food shortages, the black market and economic crime* national policy companies* financial reforms.